Strategi Pemerintah Dalam Menyetarakan Hubungan Tauke di Desa Malang Rapat Kabupaten Bintan - Yennita, Yennita; Samin, Rumzi; Prastya, Imam Yudhi (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2020)
Poverty of fishermen in Malang Village Meeting is a common phenomenon that often occurs. In a situation like this, some fishermen need a tauke who has a large capital. that's where the client patron relationship occurs. This study aims to evaluate the government's strategy to overcome the patron-client relationship (case study of the relationship between fishermen and businessmen in Malang Village Meeting, Bintan Regency). The theory used in this study uses William N. Dunn's Policy Evaluation which states that to measure the success of a program evaluation can be measured through 6 variables, namely Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, Accuracy. This research uses descriptive type method with a qualitative approach. The informants of this study were the Bintan Regency Fisheries Office, Malang village head Meeting, the head of the fishermen group, the secretary of the fishermen group, the local community / fishermen and the tauke. The data analysis technique was done by collecting data, presenting data, drawing conclusions and verifying data. The results of this study indicate that the government's strategy to overcome the patron-client relationship in MalangRapat Village is: 1. The effectiveness of beneficiaries is very beneficial for fishermen because it can increase their catch and can help with family finances. 2. Efficiency, namely regarding the aid budget. The government has the budget and has the authority to meet the needs of fishermen. 3. Adequacy that the community is greatly helped by the assistance, but lacks in Human Resources (HR). 4. Equitable distribution, namely the distribution of aid cannot be said to be effective, because there are still fishing communities who have not received assistance. 5. Responsiveness, namely the response of the fishing community is very positive for assistance and support, care, and understand well the purpose of the assistance. 6. A stipulation that this assistance program is appropriate to run because the purpose of this program is very valuable for poverty alleviation for fishing communities. In conclusion, the patron-client relationship cannot just be broken, because of the hereditary relationship between the tauke and the fisherman. but this relationship can be reduced with the assistance that has been provided by the government.